Optimasi Parameter Proses Bubut Material ST 60 dengan Pendinginan Ramah Lingkungan Menggunakan Metode Taguchi-Grey - Pamuji, Dian Ridlo; Lusi, Nuraini (Jurnal Rekayasa Mesin, 2019)
Every production process always needs to produce high quality with high productivity. However, in machining processes, qualities such as surface roughness and productivity such as material removal rates have different characteristics. Surface roughness has the quality characteristics smaller the better, while the material removal rate has larger the better. Therefore, determining the combination of lathe parameters is very important to get optimal results. A study has been carried out to determine the combination of lathe process on ST 60 material with an environmentally friendly cooling method to minimize surface roughness response and maximize material processing rates simultaneously. The coolant (cold soluble oil and air pressure), spindle rotation (550 rpm, 700 rpm and 1200 rpm), feed motion (0.053 mm / rev., 0.103 mm / rev and 0.161 mm / rev) and depth of cut (0.125 mm, 0.25 mm and 0.5 mm) were used as process parameters. The tool used in this study is a CNMG insert tool with a 0.4 mm corner radius. The experimental design was determined using the Taguchi method in the form of orthogonal matrix L18 (21x33). The optimization method used is the grey relational analysis. The results showed that an optimal surface roughness response and material removal rate obtained by setting the coolant process at level 1 of cold soluble oil, spindle rotation was set at level 3 at 1200 rpm, feeding motion was set at level 3 of 0.161 mm / rev. And the depth of cut is set at level 3 of 0.5 mm.